A study on greater trochanter reconstruction in unstable inter trochanteric fracture of femur - Sharan, Sudhir; P. N., Kartik; Jadhav, Shivsagar (International Journal of Research in Orthopaedics, 2023)
Background: A study on greater trochanter reconstruction in unstable intertrochanteric femur fracture. Methods: The 2019 to 2022, Patients were randomly divided into two groups with the help of computer-generated coded envelopes; Group A (unstable intertrochanteric femur fracture patients treated by hemi-arthroplasty or PFN with greater trochanter reconstruction) and Group B (unstable intertrochanteric femur fracture Patients Treated by hemi-arthroplasty or PFN with no greater trochanter reconstruction) with 20 patients in each group Outcomes were evaluated based on Harris hip score calculated at 2 weeks 6 weeks 3 months and 6 months. Results: Most common surgery in study groups performed were PFN, on radiology as non-union and union, most common study participants show union, on follow up at 2,6 weeks,3 months and 6 months Harris hip score was calculated and it was found to be statistically significant suggestive of improved quality of life, on radiological evaluation all cases shows non-displacement of GT position but in follow-ups at 6 weeks, 3 months and 6 months one case each reported displaced implant. Conclusions: The result of our study shows that there is improved quality of life and significant improvement in Harris hip score after reconstruction of greater trochanter in unstable intertrochanteric femur fracture.